Analysis of Consumer Decisions in Using Internet Services - Sewaka, Iwan (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
In the digital era, technology has become one of the necessities of life, one of which is the internet. In everyday life, many activities are carried out using the internet such as modes of transportation, communication, learning, household fees, and so on. This condition is an opportunity that must be seized, however, business actors must be able to attract consumers by presenting various services and promotions as an allure. This study aims to analyze the decision to use the internet services of PT. Dwi Tunggal Putra by paying attention to promotion factors and service quality as determinant variables. The research method uses qualitative techniques, where research conclusions are obtained through statistical data. The research data obtained from the results of distributing questionnaires to 100 customers of PT. Men's Dual Singles. The data were then analyzed using statistical regression techniques. The results of the study explain that the determination of promotion and service quality is 49%. This illustrates, half of consumer decisions to use internet services due to promotion and good service. As the result of partial statistics, it is known that promotion has an estimated influence value of 0.346 and service quality of 0.562 with a significant probability. This means that consumers are likely to decide to use internet services from PT. Dwi Tunggal Putra is influenced by services and promotions.